2008
DOI: 10.1177/0885066608321246
|View full text |Cite
|
Sign up to set email alerts
|

Argatroban Anticoagulation in Intensive Care Patients: Effects of Heart Failure and Multiple Organ System Failure

Abstract: We retrospectively evaluated argatroban dosing patterns, clinical outcomes, and the effects of heart failure and multiple organ system failure on dosing requirements in 65 adult, intensive care patients administered argatroban anticoagulation for clinically suspected heparin-induced thrombocytopenia (n=56) or history of heparin-induced thrombocytopenia (n=9). Argatroban was initiated then titrated to achieve target activated partial thromboplastin times 1.5 to 3 times normal control (ie, 42-84 seconds). Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 33 publications
5
37
1
Order By: Relevance
“…Liver failure was present in 3.1% of the patients in that study. 29 In the study reported here, critically ill patients had initial doses of 0.5 to 5 µg/kg per minute and required the greatest number of dosage reductions, relative to patients with hepatic or renal dysfunction or acute cardiac disease. These results are consistent with reports of lower dosing of argatroban for critically ill patients.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Liver failure was present in 3.1% of the patients in that study. 29 In the study reported here, critically ill patients had initial doses of 0.5 to 5 µg/kg per minute and required the greatest number of dosage reductions, relative to patients with hepatic or renal dysfunction or acute cardiac disease. These results are consistent with reports of lower dosing of argatroban for critically ill patients.…”
Section: Discussionmentioning
confidence: 84%
“…Small studies and case series of 4 to 65 patients have reported maintenance doses of 0.125 to 0.91 µg/kg per minute. 17,18,20,29 Conversely, initial infusions of 1.5 to 2 µg/kg per minute in these patients have resulted in supratherapeutic aPTTs and bleeding. 17,18 One group of authors suggested that passive hepatic congestion, accumulation of metabolites, and/or interactions with multiple medications used in the ICU may justify lower dose requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of heart failure and multiple organ system failure on argatroban dosing was evaluated retrospectively in intensive care patients receiving argatroban therapy owing to a suspicion or history of HIT [26]. A reduced dose of argatroban (~1 µg/kg/min) was shown to provide adequate anticoagulation in intensive care patients.…”
Section: Heart Failure and Multiple Organ System Failurementioning
confidence: 99%
“…In the prospective studies from which the analysis population was identified, patients with hepatic dysfunction were excluded and ejection fractions were not recorded. At the levels of anticoagulation used in the non-interventional setting, argatroban dose requirements are reduced in patients with hepatic dysfunction [6,30] or conditions such as heart failure or multiple organ system failure that may indirectly affect hepatic function via decreased perfusion [1,31]. It is possible that such morbidities may have contributed to the supratherapeutic ACTs observed in some argatroban-treated patients during PCI, although this remains to be evaluated.…”
Section: Limitationsmentioning
confidence: 99%